A rare case of giant adrenocortical carcinoma: a case report - Bansod, Atish N.; Satpudke, Mauktik; Hakim, Yusuf; Sawase, Niteen; Singh, Aryant Pratap; Nande, Yugal (International Surgery Journal, 2025)
Adrenocortical tumors are rare, and when large, they are often referred to as incidentalomas if detected during evaluation for unrelated symptoms. These tumors may be nonfunctional or have subtle clinical presentations, posing diagnostic and management challenges. A 50-year-old male presented with a seven-day history of dull, aching pain in the right hypochondrium, associated with a sensation of fullness in the right upper abdomen. Physical examination revealed a palpable mass in the right hypochondrium. Based on clinical evaluation, mass was suspected to be an adrenocortical malignancy. Contrast-enhanced computed tomography (CECT) identified a well-circumscribed, heterogeneous mass measuring 11×9×10 cm arising from the right adrenal gland. Hormonal workup demonstrated no functional activity, and the mass was considered an incidentaloma. The patient underwent open surgical excision of the tumor. Intraoperative findings revealed a well-encapsulated mass with no invasion of surrounding structures. Histopathological evaluation confirmed an adrenocortical carcinoma (Weiss score >3). Postoperative recovery was uneventful, and follow-up imaging at six months showed no signs of recurrence or metastasis. This case highlights the importance of evaluating incidentalomas, particularly large adrenal masses, for their potential clinical significance. Timely surgical intervention and histopathological confirmation are essential for ensuring favourable outcomes in such cases.